2017
DOI: 10.15255/cabeq.2015.2311
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Casein Fractions – Comparison of Commercial Casein and Casein Extracted from Cow’s Milk

Abstract: Biopolymer casein was isolated from cow's milk by acid coagulation, which was initiated by acetic acid and sodium acetate in the first, and hydrochloric acid in the second process. The casein isolated by acid coagulation, i.e. by first process, and commercial casein were separated on α-, β-, (α+κ)-and κ casein by urea fractionation. The aim of this study was to compare various properties of commercial casein fractions with casein fractions isolated from cow's milk. The structure of casein and casein fraction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…The microstructural images obtained for the CC and CGS matrices were similar to the previous reports that represented uniformly distributed probiotic strains within the interconnected protein matrices (Heidebach et al, 2010). Several studies also concluded that freezedrying resulted in shrunken and wrinkled matrices with rough surfaces and low porosity, which is in line with our current findings (Ptiček Siročić et al, 2016). Camel skin gelatin alone or in combination with CC displayed a microstructure consisting of crosslinked protein network somehow close to the microstructure of gelatin gels.…”
Section: Microstructural Featuressupporting
confidence: 90%
“…The microstructural images obtained for the CC and CGS matrices were similar to the previous reports that represented uniformly distributed probiotic strains within the interconnected protein matrices (Heidebach et al, 2010). Several studies also concluded that freezedrying resulted in shrunken and wrinkled matrices with rough surfaces and low porosity, which is in line with our current findings (Ptiček Siročić et al, 2016). Camel skin gelatin alone or in combination with CC displayed a microstructure consisting of crosslinked protein network somehow close to the microstructure of gelatin gels.…”
Section: Microstructural Featuressupporting
confidence: 90%
“…In addition, characteristic peaks of casein appear at 2920 and 2850 cm −1 due to symmetric and antisymmetric stretching of CH 2 . They indicate the presence of amino acids such as lysine [28]. The C=O stretching also appears at 1728 cm −1 .…”
Section: Characterization Of N-cdsmentioning
confidence: 96%
“…Thermal properties can reflect the chemical composition and structure of polymers (Ptiček Siročić et al, 2016). To study the effects of SL on the thermal properties of WP and PWP, DSC was performed and results are shown in Figure 6.…”
Section: Thermal Properties Of Wp or Pwp In The Presence Of Slmentioning
confidence: 99%